Dinamika Identitas dan Religiusitas pada Branding Halal di Indonesia - Nikmatul Masruroh (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
The term “halal” (ḥalāl) is now not only the domain of religious studies but also has implications for socio-economic studies. Halal discourse finds space for debate in lecture studies, seminars, and conferences both at local and international levels. The business sector also gives serious attention to the halal labelling of the products produced. It is a fact that halal claims have become widespread and become a product phenomenon not only in Indonesia, but also in the world. This phenomenon needs to be seen and examined whether it is as a form of religious awareness and obedience or just a business-oriented trending calculation. By using Habermas’ critical theory, this study reveals that “halal” can be interpreted as a phenomenon of identity disclosure both in religious, social, and state life. “Halal” is not only related to the issue of whether or not it is permissible, but also has an influence on various lines of life, whether religious, social, cultural, political, or economic. In addition, this study also reveals that the “halalization” of products, both goods and services, raises halal consumption behaviour as a form of religious obedience, even though this is not actually a measure of the religiosity of a religious community.